2001
DOI: 10.1182/blood.v97.10.2948
|View full text |Cite
|
Sign up to set email alerts
|

Larger numbers of CD4bright dendritic cells in donor bone marrow are associated with increased relapse after allogeneic bone marrow transplantation

Abstract: Relapse is the major cause of death after allogeneic bone marrow transplantation (BMT). This study tested the hypothesis that the numbers of donor mononuclear cells, lymphocytes, and CD34 ؉ cells influence relapse and event-free survival (EFS) after BMT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
80
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(81 citation statements)
references
References 41 publications
1
80
0
Order By: Relevance
“…A more interesting speculation may be drawn from observations of Chaperot et al 10 who demonstrated that cultured leukemic cells of CD4 þ CD56 þ hematodermic neoplasms can manifest plasmacytoid dendritic cell-like immunologic properties, including upregulation of costimulatory molecules and antigen presentation to T cells. The ability of BDCA-2 expressing plasmacytoid dendritic cells to induce Th2 immunity and the association of donor plasmacytoid dendritic cells with decreased allo-reactivity of donor T-cells after allogeneic bone marrow transplantation 26 suggest the hypothesis that the CD4 þ CD56 þ malignant counterpart of plasmacytoid dendritic cell may have capacity for antigen presentation and ability to induce Th2 and anergic immune responses in vivo. In short, these properties could yield decreased antitumor immune responses in patients with BDCA-2-positive, TdT-negative 'more mature' tumors that are induced by the tumor itself.…”
Section: Discussionmentioning
confidence: 99%
“…A more interesting speculation may be drawn from observations of Chaperot et al 10 who demonstrated that cultured leukemic cells of CD4 þ CD56 þ hematodermic neoplasms can manifest plasmacytoid dendritic cell-like immunologic properties, including upregulation of costimulatory molecules and antigen presentation to T cells. The ability of BDCA-2 expressing plasmacytoid dendritic cells to induce Th2 immunity and the association of donor plasmacytoid dendritic cells with decreased allo-reactivity of donor T-cells after allogeneic bone marrow transplantation 26 suggest the hypothesis that the CD4 þ CD56 þ malignant counterpart of plasmacytoid dendritic cell may have capacity for antigen presentation and ability to induce Th2 and anergic immune responses in vivo. In short, these properties could yield decreased antitumor immune responses in patients with BDCA-2-positive, TdT-negative 'more mature' tumors that are induced by the tumor itself.…”
Section: Discussionmentioning
confidence: 99%
“…9 Therefore, it appears very important that future studies may address the question of whether DC2 included in the graft, as well as DC2 recovery after allogeneic transplantation of hematopoietic stem cells, may correlate with hematological and immunological reconstitution, infectious events, GVHD or graft rejection episodes after transplant. For example, an initial study by Waller et al 15 suggested that a higher content of CD3 Ϫ CD4 bright DC2 in the graft would correlate with chronic GVHD and relapse after allogeneic bone marrow transplant. Monitoring of circulating DC2 numbers might also be of clinical importance in settings other than HSCT, as recently proposed for HIV patients.…”
Section: Discussionmentioning
confidence: 99%
“…[42][43][44] Lonial et al 45 recently reported slower T-cell recovery in patients receiving higher numbers of G-CSF-mobilized pDCs within the graft; further, high content of DCs in BM graft, but not in PBSC, have been associated with increased incidence of disease relapse. 46 These data have raised the concern that DC-mediated G-CSF action on mobilized T cells could impair their anti-leukemic activity. However, mobilized lymphocytes maintain their GVL effect via different pathways, 47 and Abbi et al 48 recently showed that G-CSF-mobilized donor lymphocyte infusions possess similar therapeutic activity compared with conventional unmobilized donor lymphocyte infusions.…”
Section: Allogeneic Graft Immune Cell Subsets and Tolerancementioning
confidence: 99%